1995
DOI: 10.1002/ana.410370613
|View full text |Cite
|
Sign up to set email alerts
|

Movement‐related cortical potentials preceding repetitive and random‐choice hand movements in parkinson's disease

Abstract: The movement-related cortical electroencephalographic potential was recorded from scalp electrodes in 8 patients with idiopathic Parkinson's disease studied at least 12 hours after withdrawal of their normal drug therapy, and compared with the results from a group of 8 age-matched control subjects. Two types of self-paced voluntary arm movements were examined: repetitive forward movement of a joystick, and random-choice movements of the same joystick in which subjects had to choose freely the direction in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 13 publications
2
37
0
Order By: Relevance
“…29,31,32 These findings and the rTMS results reported here do not necessarily conflict. The reduced facilitation from the nonprimary cortical motor areas could readily explain why rTMS fails to increase the size of the MEPs in PD.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…29,31,32 These findings and the rTMS results reported here do not necessarily conflict. The reduced facilitation from the nonprimary cortical motor areas could readily explain why rTMS fails to increase the size of the MEPs in PD.…”
Section: Discussionsupporting
confidence: 56%
“…Reduced cortical activity agrees with abnormal electroencephalographic (EEG) data observed in PD patients, and abnormal recordings of brain activity preceding voluntary movements. [25][26][27][28][29] In an earlier study testing the excitability of cortical motor areas with paired shocks delivered at long interstimulus intervals (100-200 msec), we found a more inhibited test response in patients with PD. 19 Because spinal mechanisms are unlikely to act at intervals greater than 100 msec, in normal subjects the inhibition observed at long interstimulus intervals probably arises from increased intracortical inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a significant dysfunction of the motor neural networks, even in patients with few symptoms. This finding is consistent with previous descriptions of reduced amplitude of BP preceding other movements in PD patients, even in the early stages 12,22,23,24,25,26 . It is also in accordance with the early clinical finding of paucity of facial expression and reduced blink rate in PD patients, suggesting that neural systems related to motor planning, especially those related to facial expression and blinks, are affected early in PD…”
Section: Discussionsupporting
confidence: 93%
“…Although most studies have reported smaller BP amplitudes in PD patients compared to normal controls, some studies have reported no differences 21,24,26 or even larger amplitudes 27,28 . The reasons for these discrepancies are not clear.…”
mentioning
confidence: 96%
“…Nevertheless, very likely this work will improve our understanding of preparatory volitional motor activity in motor cortico-cortical networks and its modification by brain stimulation. This knowledge will pertain to clinical applications for treatment of patients in whom this activity is disordered, such as in dystonia [Deuschl et al, 1995], Parkinson's disease [Touge et al, 1995], spino-cerebellar ataxia [Lu et al, 2008], traumatic brain injury [Wiese et al, 2004], or cerebral stroke [Green et al, 1999].…”
Section: Introductionmentioning
confidence: 99%